2018
DOI: 10.2340/00015555-2789
|View full text |Cite
|
Sign up to set email alerts
|

Brachioradial Pruritus and Notalgia Paraesthetica: A Comparative Observational Study of Clinical Presentation and Morphological Pathologies

Abstract: Brachioradial pruritus (BRP) and notalgia paraesthetica (NP) represent 2 of the most common neuropathic itch syndromes. A total of 58 consecutive patients presenting at the Center for Chronic Pruritus, University Hospital Münster, were analysed with regard to clinical presentation, anatomical and morphological pathologies, impairment in quality of life, and response to treatment with topical capsaicin. Patients with BRP reported stinging and burning more often than those with NP. In the BRP group structural ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
1
27
0
3
Order By: Relevance
“…17,9,11 While 27% of patients require another patch applied at three months, and 13.7% another at six months, all patients noted a significant improvement in QOL. 9,11 Side effects include intense burning, which can be mitigated by pre-treatment with topical lidocaine. 17 Other topicals studied for BRP include amitriptyline 1%/ketamine 0.5% cream, topical steroids, doxepin cream and local anesthetics.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…17,9,11 While 27% of patients require another patch applied at three months, and 13.7% another at six months, all patients noted a significant improvement in QOL. 9,11 Side effects include intense burning, which can be mitigated by pre-treatment with topical lidocaine. 17 Other topicals studied for BRP include amitriptyline 1%/ketamine 0.5% cream, topical steroids, doxepin cream and local anesthetics.…”
Section: Resultsmentioning
confidence: 96%
“…Two prospective cohort studies and one case series (n=30), have reported on its effective use in BRP after one hour of application. 9,11,17 One study described an 85% reduction in itch as soon as three weeks post-treatment and lasting three months, while two others reported a statistically significant decrease in pruritus six months after treatment . 17,9,11 While 27% of patients require another patch applied at three months, and 13.7% another at six months, all patients noted a significant improvement in QOL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a school of thought that an increase of intraepidermal nerve fibres (IENF) is a cause of itch while decrease in IENF improve itch . However our and other groups’ extensive studies in imaging of nerve fibres in skins of humans in dermatoses, such as atopic dermatitis, nummular eczema, psoriasis, cutaneous T cell lymphoma, lichen amyloidosis, prurigo nodularis, stasis dermatitis, and brachioradial pruritus, demonstrated the opposite (Table ): in those patients with chronic itch, a decrease in IENF is noted compared with healthy controls, which normalizes when itch is treated and improved. Pogatzki‐Zahn et al recently demonstrated that, in addition to decreased IENF, a mixed peripheral and central pattern of neuronal alterations was observed in patients with atopic dermatitis, brachioradial pruritus, and prurigo nodularis and might contribute to the chronicity of pruritus in these dermatoses.…”
Section: Peripheral C Nerve Fibres and Itch: Does The Number Of Nervementioning
confidence: 88%